Health-related quality of life in children and adolescents living with Gaucher disease and their parents. Issue 1 (1st January 2018) - Remor, Eduardo; Baldellou, Antonio
ABSTRACT: Objective: The health-related quality of life (HRQoL), clinical status and perceived burden of disease in children and adolescents with Gaucher Disease (GD) were assessed. Method: A Spanish multicenter collaboration study involving 13 hospitals was performed to evaluate pediatric patients with GD ( n  = 17, ages 5–18; n  = 3, ages 2–4) and their parents ( n  = 20) using a HRQoL measure (PedsQL 4.0) and a survey on the perceived burden of the disease. Three children under five years old were evaluated by parent proxy-report. Relevant medical and socio-demographical characteristics were recorded. Results: Sixty-nine percent of the participants with GD had mild and 31% had moderate severity level, all receiving enzyme replacement therapy (ERT). HRQoL was associated with the severity score index and was adjusted for age. Age was related to school functioning (older patients had lower scores), and female patients reported worse school functioning than males. Symptoms such as bone, joint or abdominal pain, bleeding, and fatigue were negatively associated with HRQoL. Perceptions of the burden related to GD, such as feeling ill and feeling sad, were negatively associated with HRQoL. Although the PedsQL scores of children and parents showed concordance, patterns of association between symptoms and perceived burden differed between children and parents. No associations were observed between HRQoL scores and time on ERT or ERT dosage. Conclusion: HRQoL perceptions were affected by clinical status, observable and subjective symptoms, feelings of burden related to the disease, and patient characteristics (e.g. age and gender). Aspects of the disease that affect HRQoL may be perceived differently by children and parents.